The art of The Mitchells vs the machines - Zahed, Ramin (New York : Abrams, 2021)
"The Art of The Mitchells vs. The Machines gives insight into how the filmmakers behind Sony Pictures Animation's new movie The Mitchells vs. The Machines were able to bring a fresh, new vision to the screen through concept art, sketches, and early character designs. The book also features exclusive commentary from director/cowriter Michael Rianda and codirector/cowriter Jeff Rowe, alumni of the team behind Emmy Award-winning Gravity Falls, and producers Phil Lord and Christopher Miller, the innovative and creative minds behind The LEGO Movie and the Academy Award-winning Spider-Man: Into the Spider-Verse."--
Introduction: Getting the team together -- Team snapshots. Guillermo Martinez: Head of story ; Lindsey Olivares: Production designer ; Toby Wilson: Art director ; David R. Bleich: Lead color designer ; Alan Hawkins: Head of character animation ; Mike Lasker: VFX supervisor -- The Mitchells. The family ; Katie ; All about "Katie vision" ; Rick ; Linda : Aaron ; Monchi ; The Mitchells' house ; Katie's bedroom ; Aaron's bedroom ; The Poseys ; Faces in the crowd ; Road trip -- Interlude. Dino stop and gift shop attack -- The machines. Brave new world ; Mark Bowman ; PAL Labs ; PAL ; The robots ; Eric and Deborahbot 5000 ; The mall of the globe ; When toys attack ; The stealthbots ; Robot city ; The rocket ; Human fun pods ; The defeat of the machines ; Katie calls from college ; Conclusion.
"Sony Pictures Animation."
Keywords: Mitchells vs the machines (Motion picture) -- Illustrations; Animated films -- United States